Virtual Watershed System: A Web-Service-Based Software Package For Environmental Modeling - Rui Wu; Connor Scully-Allison; Moinul Hossain Rifat; Jose Painumkal; Sergiu Dascalu; Jr. Frederick C Harris (Advances in Science, Technology and Engineering Systems Journal, 2018)
The physically-based environmental model is a crucial tool used in many scientific inquiries. With physical modeling, different models are used to simulate real world phenomena and most environmental scientists use their own devices to execute the models. A complex simulation can be time-consuming with limited computing power. Also, sharing a scientific model with other researchers can difficult, which means the same model is rebuilt multiple times for similar problems. A web-service-based framework to expose models as services is proposed in this paper to address these problems. The main functions of the framework include model executions in cloud environments, NetCDF file format transmission, model resource management with various web services. As proof of concept, a prototype is introduced,implemented and compared against existing similar software packages. Through a feature comparison with equivalent software, we demonstrate that the Virtual Watershed System (VWS) provides superior customization through its APIs. We also indicate that the VWS uniquely provides friendly, usable UIs enabling researchers to execute models.
Keywords: Web-based Virtual Watershed; System; Model as service; Cloud-based application; Hydrologic model